Soft Tissue Structure Modelling for Use in Orthopaedic Applications and Musculoskeletal Biomechanics. (14th December 2009) - Audenaert Audenaert, E. A. E. A.; Mahieu Mahieu, P. P.; van Hoof van Hoof, T. T.; Pattyn Pattyn, C. C.
Abstract : We present our methodology for the three-dimensional anatomical and geometrical description of soft tissues, relevant for orthopaedic surgical applications and musculoskeletal biomechanics. The technique involves the segmentation and geometrical description of muscles and neurovascular structures from high-resolution computer tomography scanning for the reconstruction of generic anatomical models. These models can be used for quantitative interpretation of anatomical and biomechanical aspects of different soft tissue structures. This approach should allow the use of these data in other application fields, such as musculoskeletal modelling, simulations for radiation therapy, and databases for use in minimally invasive, navigated and robotic surgery.